Litter Fall in A Primary and Two Logged-over Lowland Tropical Rainforests in Pasirmayang, Jambi. - UPIK ROSALINA WASRIN; AGUS EKA PUTERA (SEAMEO BIOTROP, 1999)
Litter accumulation in a primary and a logged-over lowland dipterocarp forest at Pasirmayang, Jambi was measured using the litter trap method. In the primary forest, traps were placed in four distinct areas, reflecting the succession stages of the forest from building to maturation. In the logged-over forest, litter production was measured at two different sites, one cut in 1979/1980 and the second in 1983/1984. In the primary forest, average litter production during the observation period was 925 g m